DEVELOPMENT AND BIOLOGICAL TESTING OF NEW SCAFFOLDS FROM BIODEGRADABLE MATERIALS - V. N. Vasilets; L. M. Zaitov; A. Y. Milentev; S. L. Nedoseev; P. V. Shvartskopf; V. A. Egorova; V. I. Sevastjanov (Вестник трансплантологии и искусственных органов, 2010)
The new gel-sublimation technique for preparation porus biodegradable scaffolds (hydroxybutyrate-co-hydro- xyvalerate) is presented. The scaffolds with multi-mode internal structure have the of porus sizes varied from ~100 microns up to ~100 nanometers and the porosity in a range of 80–90%. A few techniques for modification of 3D scaffolds by gas discharge plasma are developed and optimized: the microsecond dielectric barrier dischar- ge, the semi-self-maintained discharge supported by an electron beam; the nanosecond dielectric barrier dischar- ge. Biological tests including red blood cell hemolysis and cytotoxicity analysis have shown the possibilities of scaffolds applications for cell-based technologies.